2020
DOI: 10.1186/s12860-020-00259-0
|View full text |Cite
|
Sign up to set email alerts
|

ILK supports RhoA/ROCK-mediated contractility of human intestinal epithelial crypt cells by inducing the fibrillogenesis of endogenous soluble fibronectin during the spreading process

Abstract: Background: Fibronectin (FN) assembly into an insoluble fibrillar matrix is a crucial step in many cell responses to extracellular matrix (ECM) properties, especially with regards to the integrin-related mechanosensitive signaling pathway. We have previously reported that the silencing of expression of integrin-linked kinase (ILK) in human intestinal epithelial crypt (HIEC) cells causes significant reductions in proliferation and spreading through concomitantly acquired impairment of soluble FN deposition. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 95 publications
3
12
0
Order By: Relevance
“…33 In literature, an increased HFN7.1 antibody binding to unfolded FN has been described. 14,59 In our study, especially samples A and D showed a high level of accessible cell binding domain indicating an extended FN conformation. However, our data suggest that the accessibility of the cell-binding-domain is not necessary and is solely associated with the conformational change, but also with the orientation of the protein.…”
Section: Discussionsupporting
confidence: 51%
“…33 In literature, an increased HFN7.1 antibody binding to unfolded FN has been described. 14,59 In our study, especially samples A and D showed a high level of accessible cell binding domain indicating an extended FN conformation. However, our data suggest that the accessibility of the cell-binding-domain is not necessary and is solely associated with the conformational change, but also with the orientation of the protein.…”
Section: Discussionsupporting
confidence: 51%
“…In vivo, motile cells integrate various inputs from the extra-cellular matrix, and, then, adjust their migration mode 61 . Gagné et al 62 showed that ILK potentiated intestinal epithelial cell spreading and migration by allowing fibronectin fibrillogenesis. The assembly of new roads built up by the cells themselves can be also crucial in the context of collective cell migration where the remodelling of ECM by leader cells can provide a path for follower cells 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Several works have shown that cells are able to produce and to remodel their extra-cellular matrix 35,37,62,[64][65][66] . In this study, we have shown that cells actually deposit fibronectin in the form of small puncta but other ECM components may play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Two questions remain open: the nature of the footprint and the physical mechanism by which the cell is attracted back. Several works have shown that cells are able to produce and to remodel their extra-cellular matrix 35,61,63,64,65,66 . In this study, we have shown that cells actually deposit fibronectin in the form of small puncta but other ECM components may play a role.…”
mentioning
confidence: 99%
“…Gagné et al . 61 showed that ILK potentiates intestinal epithelial cell spreading and migration by allowing fibronectin fibrillogenesis. The assembly of new roads built up by the cells themselves can be also crucial in the context of collective cell migration where the remodeling of ECM by leader cells can provide a path for follower cells 62 .…”
mentioning
confidence: 99%